Exploring function and effective connectivity of the motor cortex and its role in Tourette syndrome - Pépés, Sophia (2017)
Tourette syndrome (TS) is a neurodevelopmental disorder characterised by vocal and motor tics. It is associated with cortical–striatal–thalamic–cortical (CSTC) circuit dysfunction and hyper-excitability of cortical motor regions. TS follows a developmental time course, in which tics often become increasingly more controlled during adolescence. Importantly, however, a substantial minority of patients continue to have debilitating tics into adulthood. This indicates that there may be important differences between adult TS patients and children and adolescents with the disorder.